2016
DOI: 10.1039/c6cc05717a
|View full text |Cite
|
Sign up to set email alerts
|

Nebraska Red: a phosphinate-based near-infrared fluorophore scaffold for chemical biology applications

Abstract: A series of novel phosphinate-based dyes displaying near-infrared fluorescence (NIR) are reported. These dyes exhibit remarkable photostability and brightness. The phosphinate functionality is leveraged as an additional reactive handle in order to tune cell permeability as well as provide a proof-of-principle for a self-reporting small molecule delivery vehicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
143
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 34 publications
0
143
1
1
Order By: Relevance
“…With respect to the predecessor 1 c , the performed changes of the molecular structure resulted in a remarkable 12 103 cm 1 (362 nm) bathochromic shift of fluorescence demonstrated by 6 c . It is important to note that the emission characteristics of 5 c and 6 c in organic solvents place them among the most efficient and red shifted organophosphorus dyes reported to date . The photoinduced intramolecular charge transfer leads in turn to large Stokes shifts of approximately 7600 cm −1 (280 nm, 5 c ) and 4700 cm −1 (230 nm, 6 c Figure ), minimizing the reabsorption, which is crucial for practical imaging applications…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the predecessor 1 c , the performed changes of the molecular structure resulted in a remarkable 12 103 cm 1 (362 nm) bathochromic shift of fluorescence demonstrated by 6 c . It is important to note that the emission characteristics of 5 c and 6 c in organic solvents place them among the most efficient and red shifted organophosphorus dyes reported to date . The photoinduced intramolecular charge transfer leads in turn to large Stokes shifts of approximately 7600 cm −1 (280 nm, 5 c ) and 4700 cm −1 (230 nm, 6 c Figure ), minimizing the reabsorption, which is crucial for practical imaging applications…”
Section: Resultsmentioning
confidence: 99%
“…[6] Such P = O-substituted fluorophores enable the acquisition of repeated images in stimulated emission depletion (STED) microscopy,where the fluorophores are exposed to an extremely intense depletion laser field. Indeed, the replacement of the endocyclic oxygen atom in xanthene scaffolds with aP = Om oiety generates the corresponding fluorescein (POF), [8] rhodol (PORL), [9] and rhodamine (POR) [10] derivatives ( Figure 1a), which emit fluorescence in the far-red to NIR region in PBS (pH 7.4). Indeed, the replacement of the endocyclic oxygen atom in xanthene scaffolds with aP = Om oiety generates the corresponding fluorescein (POF), [8] rhodol (PORL), [9] and rhodamine (POR) [10] derivatives ( Figure 1a), which emit fluorescence in the far-red to NIR region in PBS (pH 7.4).…”
mentioning
confidence: 99%
“…Interestingly, our studies have shown that a simple hydrolysis of a bridging phosphinate ethyl ester can yield a 37 nm blue-shift in the emission of the corresponding fluorophore. [5] This experimental observation led us to ask whether chemoselective reactions of novel functional groups in xanthene-based fluorophores could be utilized to afford ratiometric chemodosimeters displaying large shifts in both excitation and emission.…”
mentioning
confidence: 99%